Modelling and Simulation of Control Circuit for Oscillator Based Inverter for Microgrids - Ramaprabha, R.; Rithika, S. (Asian Journal of Electrical Sciences, 2014)
This paper presents a control strategy for oscillator based inverter for microgrids to enable asymptotic synchronization in order to produce a stable power system. The microgrid is formed by paralleling of three 3-phase inverters; the output of the inverter is programmed to outdo the changing aspects of a non-linear oscillator. The virtual oscillator within the controllers is implicitly coupled through physical electrical network say RLC networks and coordinate transformations. Due to the self-sustaining capability of the oscillators, the inverter ac outputs are synchronized and communication between the inverters is not needed as the controller uses local signals as feedback elements. In this paper, the methodology of the controller is framed in such a way that the inverter output voltage is retained within prescribed limits although there are fluctuations in load. The simulation results prove that the controller retains the voltage fluctuations within ± 5 %.